2005
DOI: 10.1016/j.jvs.2004.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy with a polyurethane patch versus primary closure: A prospective randomized study

Abstract: Patch angioplasty with polyester urethane significantly reduced the restenosis rate ( P = . 01) compared with primary closure. Even though clamping time was longer, patching was not associated with more perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 26 publications
(27 reference statements)
1
46
0
2
Order By: Relevance
“…Lastly, the surgical patch angioplasty method may limit restenosis after drug delivery is reduced below therapeutic levels, e.g. after the drug is exhausted, since the patched site has less tendency for form restenosis, thereby increasing the translational potential of patch angioplasty30313233.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the surgical patch angioplasty method may limit restenosis after drug delivery is reduced below therapeutic levels, e.g. after the drug is exhausted, since the patched site has less tendency for form restenosis, thereby increasing the translational potential of patch angioplasty30313233.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of patch material is affected by thrombogenicity, aneurismal formation, risk of patch rupture, availability of patch material, complications related to vein harvesting, and the resistance to infection. Some surgeons prefer harvesting autologous veins, including the saphenous vein, or the internal/external jugular vein and facial vein [8]. RCTs and animal studies support that using an intima-lined patch may potentially reduce the risk of perioperative thrombosis and infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of patch materials for closure of the arteriotomy are available, including autologous venous patch and synthetic patch materials (Dacron, polytetrafluoroethelene (PTFE), bovine pericardium, and polyester urethane) [4][8]. Currently, selection of types of patch materials depends on the surgeon’s preference, as there is no agreement on the priority of use of venous over synthetic patch materials during CEA [1].…”
Section: Introductionmentioning
confidence: 99%
“…The exclusion of such patients, likely to be predominantly female, may therefore confound the results. Indeed, one study in the meta-analysis showed female patients to be at a significantly higher risk of restenosis 14 . Our study found that female sex was considered an indication for selective patching by a proportion of surgeons.…”
Section: Discussionmentioning
confidence: 47%